GUIDELINES USING POTENTIAL STAKEHOLDERS IN ENHANCING REPRODUCTIVE HEALTH AND IDEAL MARRIAGE AGE EDUCATION IN NATIONAL POPULATION AND FAMILY PLANNING BOARD’S YOUTH INFORMATION AND COUNSELLING CENTER - Duly Apika Sari; Poschanan Niramichainont (Proceedings of the International Conference on Applied Science and Health, 2019)
Background: Reproductive health education in school seemed less concerned by the Government in Indonesia. Reproductive health was not yet inserted in the curriculum, as a result, it was implemented through the youth center inside the school, like YICC. Participation of stakeholders may contribute for enhancing this YICC,moreover, in decentralisation era in Indonesia today. Furthermore, less research about stakeholder analysis made this research was necessary to do. Aims: To map stakeholders and explore guidelines from potential stakeholders in enhancing reproductive health and ideal marriage education in National Population and Family Planning Board of Indonesia (so-called BKKBN)’s Youth Information and Counselling Center in Jakarta Province, Indonesia. Methodology: This research applied the descriptive qualitative method and used Power versus Interest grid mapping model. 27 organizations were asked in-depth interviewed and Focus Group Discussion with semi-structured questions about their power and interest to YICC in two cities in Jakarta: Center of Jakarta and East of Jakarta. Result: The results were in mapping and guidelines. In mapping stakeholders, from the 27 stakeholders in the mapping model, most of the stakeholders were in the area 3 who were placed by stakeholders in provincial and local level with characterised low power and high interest, while stakeholders in national level placed in area 1 was in high power and low interest. The guidelines recommended actions based on the area on the mapping model. These findings were prominently recommended for inputting the appropriate YICC into the system of the school for the sustainability of the programs. Conclusion: The power versus interest grid model pictured that the engagement of national stakeholders was less than provincial and local stakeholders in YICC. This program should be run under regulations between Ministry of Education and Culture for the sustainability of the YICC programs. Also, the YICC should be continuously monitored in the practical context. Keywords: Reproductive health and ideal marriage education, stakeholders analysis, Youth Information and Counselling Center